2019
DOI: 10.1111/cea.13515
|View full text |Cite
|
Sign up to set email alerts
|

Can dietary strategies in early life prevent childhood food allergy? A report from two iFAAM workshops

Abstract: Food allergy affects a small but significant number of children and adults. Food allergy is responsible for considerable morbidity and is the commonest cause of anaphylaxis in children. One of the aims of the European Union‐funded “Integrated Approaches to Food Allergen and Allergy Risk Management” (iFAAM) project was to improve our understanding of the best way to prevent the development of food allergy. Groups within the project worked on integrating the current prevention evidence base as well as generating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…We need to wait a little longer for the food allergy results from the Preventall study. Please keep safe in the midst of the CORVID‐19 pandemic 8,9 …”
Section: High Fev1 (N = 13) Low Fev1 (N = 14) Control (N = 10) P‐valuementioning
confidence: 99%
“…We need to wait a little longer for the food allergy results from the Preventall study. Please keep safe in the midst of the CORVID‐19 pandemic 8,9 …”
Section: High Fev1 (N = 13) Low Fev1 (N = 14) Control (N = 10) P‐valuementioning
confidence: 99%
“…We know that heat can alter the allergenicity of food proteins 8 . Graversen et al look at whether the heat treatment of a whey‐based protein changes allergenicity, tolerogenicity and intestinal uptake in animal models 9 .…”
Section: Figurementioning
confidence: 99%
“…The first from Roberts and colleagues summarized two iFAAM workshop, the large EU project that has done much to advance our management of food allergy. 12 The second is a systematic review from Burgess and colleagues. 35 Their synthesis of the randomized controlled trial data indicated that introducing egg from 4 to 6 months and peanut from 4 to 11 months reduced the risk of egg and peanut allergy, respectively.…”
Section: Food Allergy: Prevention and Managementmentioning
confidence: 99%
“…Other important early life exposures that may have an impact on asthma and allergic disease include exposure to diet and microbiota. In a report from two iFAAM workshops, the role of dietary strategies to prevent childhood food allergy was summarized 12 and Mensink‐Bout reported on the association between maternal and neonatal 25‐hydroxyvitamin D concentrations and school‐age lung function, asthma and allergy from the Generation R Study 13 . Helminth exposure however does not seem to be important for the difference in allergy‐related outcomes between rural and urban communities 14 and the association between season of birth, childhood asthma and allergy to be mediated by lower respiratory infections 15 …”
Section: Epidemiologymentioning
confidence: 99%